The law and ethics of medicine essays on the inviolability of human life - Keown, John. (Oxford : Oxford University Press, 2012)
The principle of the sanctity of life is key to the law governing medical practice and ethics. It is also widely misunderstood. This book clarifies the principle and considers how it influences the law governing abortion; test-tube babies euthanasia; feeding patients in persistent vegetative states and palliative treatment.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: Medical ethics; Medical laws and legislation; Right to life